EXPERIENCE OF ALPROSTADIL APPLICATION AGAINST RAYNAUD'S SYNDROME AMONG CHILDREN - E.I. Alexeeva; S.I. Valieva; K.B. Isaeva; R.М. Denisova (Вопросы современной педиатрии, 2007)
The article provides the data on the causes and mechanisms of Raynaud's syndrome development. initial or idiopathic Raynaud's syndrome is characterized by the spasm of the digital arteries and thermoregulatory vessels of skin under the impact of the cold without any signs of vessel lesions. In the event of secondary Raynaud's syndrome, there is combination of Raynaud's syndrome with the symptoms of other diseases. Secondary raynaud's syndrome is most often associated with scleroderma systematica, systemic erythema centrifugum, other rheumatic diseases, hematologic disc orders and intake of some medications. There is also data on the opportunity to apply the synthetic medication prostaglandin е 1 — alprostadil to treat Raynaud's syndrome associated with rheumatic diseases. The given clinical example demonstrates high efficacy of alprostadil in case of the patient, suffering from scleroderma systematica and generalized Raynaud's syndrome.Key words: children, scleroderma systematica, alprostadil, Raynaud's syndrome.